Scaling climate information services using digital platform in Mali - Diallo, Aboubacar; Diarra, Afoussata; Dossou-Yovo, E. R. (2024)
This report presents the outcomes and lessons learned from scaling climate information services (CIS) in rice-based systems in Mali through a digital platform under the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project. The initiative leveraged a farmer-centric digital platform to deliver timely, location-specific CIS, empowering farmers with actionable insights for improved agricultural decision-making. Key features of the digital platform included integration of various CIS types, multiple access channels such as WhatsApp, SMS, calls, and the use of local languages to ensure inclusivity. In 2024, the platform reached 310,333 farmers, 45% of whom were women, contributing to increasing rice yield by 705 kg/ha, income by 345,288 XOF/ha (575 USD/ha) and food consumption score by 2 in rice-based systems. This report outlines the challenges, impacts, and scalability potential of the digital platform as a sustainable solution to enhance climate resilience in rice-based systems.